Analysis of completeness for spontaneous reporting of disease-modifying therapies in multiple sclerosis - Araujo, Ariane G. S.; Lucchetta, Rosa C. [UNESP]; Tonin, Fernanda S.; Pontarolo, Roberto; Borba, Helena H. L.; Wiens, Astrid (Taylor & Francis, 2021)
Introduction: Considering the need for effective postmarketing surveillance of disease-modifying therapies (DMTs) in multiple sclerosis (MS), we analyzed the potential of the spontaneous reports for safety signal detection, verifying the completeness of the reports in the FDA Adverse Event Reporting System (FAERS). Methods: All reports with DMTs for MS considered the primary suspect cause of ADRs and registered between January 2004 and June 2019 were selected. The vigiGrade completeness score was applied and reports with a score greater than 0.80 were considered well documented. Descriptive statistical analysis and comparisons of well-documented reports by DMTs were performed. Results: A total of 297,926 reports were analyzed. The lowest completeness rates were observed for type of report (13.5%), dose (62.7%), and time from treatment start to the ADR (79.0%). Overall, 80.8% of reports were classified as well documented and those related to natalizumab had the highest proportion (92.4%, p < 0.001), while the lowest was observed for reports sent in 2017 (53.1%, p < 0.001) and for teriflunomide (48.5%, p < 0.001). Conclusions: The high proportion of well-documented reports for DMTs indicates that they can be a valuable source for safety signal detection. A more careful analysis should be performed for data from the groups identified with low completeness to avoid the disclosure of spurious results.
Keywords: Adverse drug reaction; data accuracy; pharmacovigilance; postmarketing; product surveillance; spontaneous reporting